KERAGAMAN SPESIES DAN PROFIL ASAM LEMAK GONAD LANDAK LAUT (ECHINOIDEA) DI PANTAI SELATAN KABUPATEN GUNUNG KIDUL DAERAH ISTIMEWA YOGYAKARTA - , SRI ENDANG PURNAMI,SP ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Sea urchin (Echinoidea) is an invertebrate animal whose habitat can be found fromthe intertidal to shallow subtidal areas. Sea urchin has very important role in reef ecology, especially in intertidal and subtidal areas. Sea urchin gonad also can be consumedand has high economic value. The aim of this study was to detennine the speciesdiversity and profile of fatty acid Sea urchin gonad in South Coral Gunung Kidul. Sea Urchin samples were taken from five location, among of Le Krakal beach, Drini, Sepanjang, Kukup and Wediombo, using purposive sampling method. Gonad samples were taken from two sampling locations, those were four species from Sepanjangbeach and one species from Wediombo coast. Fat was separated from the gonadusing the method of Blight and Dyer and fatty acid methyl ester were prepared by direct transesterification reaction according to Morisson and Smith. Fatty acid methylester were separated and analysed by gas chromatography. The result showed there are 14 species belonging to nine genera of four families, these are Echinometra mathaei, Echinometra sp, Echinostrephus aciculatus, Heterocentrotussp.l, Heterocentrotus sp.2, Colobocentrotus sp.l, Colobocentrotus sp.2, Diadema setosom, Diadema sp.1, Diadema sp.2, Echinotrix sp.l, Echinotrix sp.2, Stomopneustesvariolaris, Tripneustes gratila dan Taxopneustes sp.. Fatty acid of Sea urchin gonad analysis can be found saturated and unsaturated fatty acids include C8:0, CI4:0, CI6:0, CI8:0, C20:0, CI8:1n-9, CI6:1n-7, CI8:2n-8 and C20: 5n-3. The level of saturatedfatty acids is higher than the unsaturated fatty acids, especially myristci acid 27.20% in Stomopneustes variolaris and palmitic acid 24.44%, while the higher of unsaturated fatty acids eicosapentaenoic acid (EPA) 14.83% , both found ini Colobocentrotussp.2. The species diversity of sea urchin in South Coral Gunung Kidul is very high. Although the fatty acids of Sea urchin gonad have similar type but they havedifferent level.